Strategic planning in property development: market evidences - Balarine, Oscar Fernando Osório (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper describes applications of strategic planning to property development, based on existing bibliography and on strategies adopted by property development companies. It concludes that several companies are using consistent strategies, and also adopting creative marketing campaigns to achieve successful results.